Ferucarbotran-loaded red blood cells as long circulating MRI contrast agents: first in vivo results in mice. (4th May 2018) - Antonelli, Antonella; Pacifico, Severina; Sfara, Carla; Tamma, Marialuisa; Magnani, Mauro
Aim: The encapsulation of superparamagnetic iron oxide contrast agents in red blood cells (RBCs) could overcome their rapid removal by reticulo–endothelial system improving their stability in blood circulation.Materials & methods: Murine ferucarbotran-loaded RBCs were tested in vivo as new contrasting agents in MRI application.Results: A superior visualization of organs and cerebral vessels was evidenced in ferucarbotran-loaded RBCs-treated mice compared with the controls. The signal enhancement lasted for days, while the contrast from bulk ferucarbotran disappeared after few minutes.Conclusion: Ferucarbotran-loaded RBCs showed to improve diagnostic imaging and their use may extend the time frame for MRI and magnetic resonance angiography since to date the time frame for data acquisition has been limited to the first pass.